ENTREPRENEURIAL RESILIENCE OF MSMES IN FACING GLOBAL ECONOMIC UNCERTAINTY: A CASE FROM INDONESIA - Dayuni Dayuni (Journal of Management Economic and Financial, 2024)
In the midst of global economic uncertainty marked by market fluctuations, geopolitical crises, and supply chain disruptions, Micro, Small, and Medium Enterprises (MSMEs) are required to have entrepreneurial resilience in order to survive and grow. This study aims to analyze the factors that shape the resilience of MSME entrepreneurs in Indonesia and the adaptation strategies they carry out in the face of economic uncertainty. Using a mixed-method approach, quantitative data was collected from 200 MSME actors through a structured survey, while in-depth interviews were conducted with 10 MSME owners from various business sectors. The research focus includes managerial capabilities, product innovation, business digitalization, and social networks as the main dimensions of resilience. The results show that MSMEs that actively adopt digital technology, strengthen business network collaboration, and invest in product innovation tend to be more resilient in the face of external pressures. In addition, government policy support and access to financing are external factors that strengthen the adaptation capacity of MSMEs. This research contributes to the literature by presenting empirical evidence on the resilience of MSME entrepreneurship in developing countries. Practically, this study offers strategic recommendations for MSME actors, policymakers, and financial institutions to strengthen the resilience of Indonesian MSMEs in facing global challenges.